Motivational values and entrepreneurial self-efficacy in the students of the professional school of management of the Universidad Privada de Huancayo Franklin Roosevelt, 2022. - Ponce Romero, Giancarlo Giovanni (2023)
The objective of this research is to analyze the relationship between motivational values and entrepreneurial self-efficacy in students of the professional school of administration of the U.P.H. Franklin Roosevelt in the year 2022. The material and method used was the scientific method with a quantitative approach, the research is of a basic, descriptive and correlational type, with a non-experimental design, the same one whose purpose was to show or examine the relationship that exists between the study variables. The Results that were obtained after the contrasting of the hypotheses, with respect to the general hypothesis, it can be affirmed that it is accepted because it was obtained as a correlation coefficient Spearman's rho = .780 ** evidencing the existence of a very strong direct relationship between motivational values and entrepreneurial self-efficacy, the same ones that were verified within the students of the professional school of administration of the U.P.H. Franklin Roosevelt in the year 2022. The Conclusions obtained from the investigation demonstrate the existence of a direct correlation between the study variables. KEYWORDS: Motivational values, entrepreneurial self-efficacy, entrepreneurs.